ENTRE O DITO E O NÃO DITO ACERCA DOS VALORES DA CULTURA ORGANIZACIONAL: O CASO DE UMA EMPRESA DE PRESTAÇÃO DE SERVIÇOS EM MANUTENÇÃO DE REDES DE MÉDIA TENSÃO - Siqueira, Douglas Murilo (2007)
This study aimed to identify the intensity of the organizational values of a familiar company in the electric services industry, how the transmission these values happens and how much they are aligned with an ideal value perception. It was appraised as "said" the legalized cultural elements. What is said and not practised for the organization they had been considered as "not said", therefore many times do not obtain to win the barrier of the document where they are express. The research, nature empirical, adopted the only case study model and adopt as main theoretical reference the Tamayo research (1996) called Organizational Values Scale. Interviews with the founder of the company and focused with the employees and their leader. It was used structuralized research of the author mentioned with some adaptations in the instructions for the company context and used statistic concepts for results. The field study was realized by systematic observation in visits carried through in the two company’s units (Osasco - SP and Jundiaí - SP). The results are presented in tables for better data visualization. The conclusion had pointed with respect to existence of values with little intensity. Strongest values are oriented for Efficiency and Effectiveness and bows relationship, both originated of the professional and personal skill of the founder. The results also show, by means of the culture components observation, low capacity of transmission of the organizational values and high non-aligned between perceived values like real and declared values like ideal. Finally are suggested new studies about the theme.(AU)